Perspektif Dalil Pendidikan Tentang Kebersihan Dan Pelestarian Lingkungan - Tunjung Magenta; Taufik Warman Mahfuzh; Ahmadi; Himad Ali (At Turots: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to describe the arguments from the Qur'an and hadith that talk about hygiene education and environmental preservation. The research method uses literature studies, data sources from the Qur'an, hadith, books, journals, the internet and other sources. Data analysis using descriptive. The results of this literature study research are that there are arguments from the Koran related to hygiene education and environmental love including two suras related to maintaining cleanliness. Then four suras are related to protecting the environment and caring for its sustainability. As for the evidence from the hadith, two hadiths mention cleanliness related to one's faith, one hadith is related to the recommendation to maintain cleanliness as much as possible and another hadith explains the things that Allah SWT likes, namely purity and cleanliness.